2019
DOI: 10.1139/apnm-2018-0801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromuscular electrical stimulation frequency on postprandial glycemia, current-related discomfort, and muscle soreness. A crossover study

Abstract: Consensus is lacking regarding optimal neuromuscular electrical stimulation (NMES) parameters for postprandial glycemic control. Therefore, the aim of this study was to determine the NMES frequency inducing the greatest hypoglycemic effect in healthy individuals. The secondary aim was to compare current-related discomfort and muscle soreness between different frequencies. We conducted an experimental clinical study with a randomized crossover design. Sixteen healthy and sedentary participants received NMES for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Similarly, performing 30 min of passive stimulation did not affect the glucose response over the three hours after the meal. These results are in contrast with previous findings that have found a reduced glucose response in diabetic and healthy sedentary individuals after 30 min of intermittent NMES [25,26]. For instance, Myiamoto et al ( 2012) have shown that in old patients with type 2 diabetes, treated with oral hypoglycemic agents, 30 min of continuous passive NMES applied with a frequency of 4 Hz on the lower limb muscles reduced the glycemic response to a meal [25].…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Similarly, performing 30 min of passive stimulation did not affect the glucose response over the three hours after the meal. These results are in contrast with previous findings that have found a reduced glucose response in diabetic and healthy sedentary individuals after 30 min of intermittent NMES [25,26]. For instance, Myiamoto et al ( 2012) have shown that in old patients with type 2 diabetes, treated with oral hypoglycemic agents, 30 min of continuous passive NMES applied with a frequency of 4 Hz on the lower limb muscles reduced the glycemic response to a meal [25].…”
Section: Discussioncontrasting
confidence: 87%
“…For instance, Myiamoto et al ( 2012) have shown that in old patients with type 2 diabetes, treated with oral hypoglycemic agents, 30 min of continuous passive NMES applied with a frequency of 4 Hz on the lower limb muscles reduced the glycemic response to a meal [25]. Similar results have been found in normoglycemic young sedentary individuals, in which 20 min of discontinuous (4 s ON and 12 s OFF) passive NMES at 5 Hz elicited a substantial reduction of post-meal blood glucose concentration [26]. Conversely, in our population (i.e., healthy young active individuals), passive NMES did not have any effect on the postmeal glycemic response.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been well established that muscle contraction effectively increases glucose uptake via an insulin-independent signaling pathway ( 14 , 15 ). Human studies on the effects of NMES-induced muscle contraction on insulin sensitivity are limited to the population with T2DM ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ) and spinal cord injury (SCI) ( 24 , 25 , 26 , 27 ). Two studies conducted in healthy individuals reported an increased acute glucose disposal rate measured by a hyperinsulinemic–euglycemic clamp ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were 22 longitudinal studies that investigated the chronic effects of NMES on glycemic control were included in this systematic review. Except for four studies that investigated young adult population ( 30 , 59 , 69 , 74 ), all studies were conducted in middle-aged and elderly men and women. Majority of the studies (n=16) reported improvement in glycemic control measured by various methods including fasting blood glucose ( 56 58 , 60 , 62 , 63 ), OGTT ( 23 , 29 , 31 , 72 , 79 ), MGTT ( 73 ), HbA1c ( 64 , 70 ), and hyperinsulinemic euglycemic clamp ( 75 , 76 ), while two studies reported no changes in glycemic control as measured by fasted blood glucose ( 65 ), and hyperinsulinemic euglycemic clamp ( 71 ).…”
Section: Resultsmentioning
confidence: 99%